Bacterial spectrum colonizing chronic leg ulcers: A 10‐year comparison from a German wound care center. (December 2014) - Jockenhöfer, Finja; Chapot, Valérie; Stoffels‐ Weindorf, Maren; Körber, Andreas; Klode, Joachim; Buer, Jan; Küpper, Bernhard; Roesch, Alexander; Dissemond, Joachim
Summary Background and Objectives Chronic wounds are colonized by many different bacteria. Patients and Methods We analyzed microbiological swabs from chronic leg ulcers from 2012/2013 and matched the results with those from 2002/2003 and 2007/2008 from the same institution. Results Results from 100 patients from our specialized wound care center were evaluated retrospectively. The etiologies were broadly variable with chronic venous insufficiency being the most common. As the most common bacterium Staphylococcus aureus was found in 53 % of patients; 9 % of patients were positive for methicillin‐resistant S. aureus (MRSA). Pseudomonas aeruginosa was detected in 25 % of patients. Different fecal bacteria and Enterobacteriaceae were found in 49 % of the patients; 11 % of the swabs were sterile. The detection rate for S. aureus has regressed by 17.1 % over the past decade and in the case of MRSA by 12.5 %. In contrast, colonization with gram‐negative bacteria species significantly increased by 11.7 %. This tendency was also seen in 2007/2008, but with a higher count of P. aeruginosa. Conclusion Although S. aureus is still the most frequently detected bacterium in our wound care center, there has been a shift in the bacterial spectrum from gram‐positive towards gram‐negative bacteria over the last decade.